2014
DOI: 10.1111/jvh.12237
|View full text |Cite
|
Sign up to set email alerts
|

Boceprevir and telaprevir‐based triple therapy for chronic hepatitis C: virological efficacy and impact on kidney function and model for end‐stage liver disease score

Abstract: Triple therapy using telaprevir or boceprevir [hepatitis C virus (HCV)-NS3/NS4A protease inhibitors (PI)] in association with PEG-IFN/ribavirin has recently become the new standard of care (SOC) for treatment of HCV genotype 1 patients. Our objective was to assess the efficacy and tolerance of triple therapy in routine clinical practice. A total of 186 consecutive HCV patients initiating triple therapy were enrolled in a single centre study. Clinical, biological and virological data were collected at baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Nevertheless, in a large cohort (1486 patients), Mauss et al[10] showed a reversible decrease of eGFR in patients taking telaprevir or boceprevir. Similar reports involving telaprevir therapy confirmed this observation and suggested a link with anemia occurrence[75-78]. Recently, Kunze et al[30] described competition between telaprevir and OCT2, which interacts with creatinine tubular transport and is involved in proximal tubular secretion.…”
Section: Specific Nephrotoxicity Of Hcv Drugssupporting
confidence: 57%
“…Nevertheless, in a large cohort (1486 patients), Mauss et al[10] showed a reversible decrease of eGFR in patients taking telaprevir or boceprevir. Similar reports involving telaprevir therapy confirmed this observation and suggested a link with anemia occurrence[75-78]. Recently, Kunze et al[30] described competition between telaprevir and OCT2, which interacts with creatinine tubular transport and is involved in proximal tubular secretion.…”
Section: Specific Nephrotoxicity Of Hcv Drugssupporting
confidence: 57%
“…The current standard of therapy for these patients is PEG-IFN/ RBV for 48-weeks. Unfortunately, less than 50% of patients respond to this therapy (20). The sustained virologic response (SVR) with telaprevir was reportedly approximately 70%-80% in previous reports (1).…”
Section: Discussionmentioning
confidence: 99%
“…This combination may cause some side effects, including itching, rash, anemia, nausea, fatigue, diarrhea, vomiting, anal or rectal problems, taste changes, and signs or symptoms of dehydration (2). More recently, renal impairment has been reported with telaprevir (20). In that report, the model for end-stage liver disease (MELD) score was also used to evaluate specific effects of treatment on liver health.…”
Section: Discussionmentioning
confidence: 99%
“…The IL28B genotype was also identified as a predictor of SVR12, with a higher probability of response among patients with the IL28B CC genotype (OR = 3.54, p = 0.031). However, since other studies have reported a limited impact of the IL28B genotype on response rates [51], further studies are needed to confirm this association more precisely [47]. …”
Section: Viral Efficacy During Phase III Trials Of Triple Therapymentioning
confidence: 99%
“…Impairment of renal function was also observed in different cohort studies for both PIs. Indeed, a significant decrease in the glomerular filtration rate was observed after the introduction of the PI but a return to normal values occurred after the end of the PI intake [46,47]. Furthermore, an increase in serum RBV concentration was observed in a group of patients treated with telaprevir [48].…”
Section: Viral Efficacy During Phase III Trials Of Triple Therapymentioning
confidence: 99%